PENGARUH AKUNTABILITAS, KOMPETENSI SDM, DAN SPI TERHADAP KUALITAS LKPD DI KOTA PALEMBANG - Adillia, Syahida; Zulkifli; Oktarida, Anggeraini (Jurnal Riset Terapan Akuntansi, 2025)
This study analyzes the influence of regional financial management accountability, human resource competence, and internal control system on the quality of financial statements of Palembang City Government, which has recently experienced a decline in BPK’s audit opinion. A quantitative method was applied through surveys of 78 financial staff across 32 regional government units, and the data were analyzed using SEM-PLS (SmartPLS 4). The findings show that all three variables have significant positive effects, with an R² value of 68.8%. These results emphasize the critical role of accountability, HR competence, and effective internal control in improving financial reporting quality, particularly in the context of Palembang’s declining audit opinion. Keywords: Accountability, Human Resource Competence, Internal Control System, Quality of Regional Government Financial Statements